Utilization of cancer immunotherapy in sub-Saharan Africa - Olatunji, Elizabeth; Patel, Saloni; Graef, Katy; Joseph, Adedayo; Lasebikan, Nwamaka; Mallum, Abba; Chigbo, Chinelo; Jaffee, Elizabeth; Ngwa, Wil (Frontiers in Oncology, 2023)
This is a provisional file, not the final typeset article 292 responses were included from 28 countries in SSA. 29% of all respondents indicated their clinic has easy access to cancer immunotherapy and 46% indicated their clinic currently practices it. Of clinics that practiced immunotherapy (n = 133), 12% used genomic sequencing to assess the tumor mutational burden biomarker, and 44% assessed expression of the PD-L1 biomarker prior to immunotherapy administration. 46% of all respondents were familiar with immunotherapy. 11% indicated being adequately trained to administer it. Of these (n=33), 52% indicated also being trained to manage immune-related adverse events related to immunotherapy administration.Immunotherapy utilization and training is low in SSA and insufficient for the rising cancer burden. Increased accessibility and usage of biomarker testing to predict immunotherapy response, incorporation of immunotherapy training into continuous medical education, and increased access to immunotherapy drugs may be prerequisites for expanded utilization of immunotherapy in SSA.